2020
DOI: 10.1186/s12889-020-09248-6
|View full text |Cite
|
Sign up to set email alerts
|

The pre-exposure prophylaxis (PrEP) consciousness of black college women and the perceived hesitancy of public health institutions to curtail HIV in black women

Abstract: Background: Consistent use of Pre-Exposure Prophylaxis (PrEP), a biomedical intervention for HIV seronegative persons, has been shown to significantly decrease HIV acquisition. Black women are a viable population segment to consider for PrEP use as their HIV incidence is overwhelmingly higher than all other women groups. Methods: We developed and piloted a cultural-and age-appropriate PrEP education intervention to determine Black college women's: 1) perceptions of and receptivity to PrEP use; and 2) preferenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 38 publications
4
71
1
Order By: Relevance
“…Hearing directly from peers about their experiences taking PrEP could help to allay specific medication-related concerns [ 19 ]. In addition, social marketing that reduces HIV- and PrEP-related stigma and communicates the relevance of PrEP to women could help to overcome social challenges and misperceptions on a broader scale [ 9 , 21 , 23 ]. Beyond addressing perceived barriers, PrEP interventions should underscore the prospective benefits of PrEP, which may be similarly or more influential to individuals’ assessment of their own PrEP candidacy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hearing directly from peers about their experiences taking PrEP could help to allay specific medication-related concerns [ 19 ]. In addition, social marketing that reduces HIV- and PrEP-related stigma and communicates the relevance of PrEP to women could help to overcome social challenges and misperceptions on a broader scale [ 9 , 21 , 23 ]. Beyond addressing perceived barriers, PrEP interventions should underscore the prospective benefits of PrEP, which may be similarly or more influential to individuals’ assessment of their own PrEP candidacy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the video was intended to be suitable for patients with minimal PrEP knowledge, rendering it appropriate for many of the patients who elected to watch it in our study—68% of women in the Web Video Condition analytic sample had never previously heard of PrEP. However, patients who are already familiar with PrEP and contemplating usage or (dis)continuation may benefit from a video incorporating other information, such as details about local HIV epidemiology, guidance on sexual health communication, or instructions for accessing PrEP financial assistance [ 9 , 14 ]. Although the majority of participants in the Web Video Condition indicated that the video held their attention, it is possible that expanding the web-based intervention to incorporate not only video viewing but also interactive elements such as games or personalized role plays could promote more active engagement [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest rates of poverty in the US are found among women, due to gender wage and wealth gaps, segregation into low-paying jobs, and inadequate or inaccessible public social assistance programs [29]. As a result, healthcare insurance may be limited, which may directly affect healthcare access and subsequent PrEP access.…”
Section: Disparities In Healthcare Access To Prep Among Womenmentioning
confidence: 99%